ANALISIS LOCATION QUOTIENT (LQ) DALAM PENENTUAN SEKTOR BASIS DAN NON BASIS DI KABUPATEN KUANTAN SINGINGI - Pratiwi, Retni (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2024)
Identifying industrial sectors and sub-sectors is one of the steps in planning the development of economic growth centers. Therefore, local quotient analysis is needed to understand how far a particular regional economic sector is specialized using its basic or leading sectors. The base sector can be determined using the Local Quotient (LQ) method. The variable used to determine the basic economic sector is the Gross Regional Domestic Product (GRDP) for regions whose activities are focused on financial structure. Gross domestic product (GDP) is an important indicator for understanding economic conditions, especially in Kuantan Singingi Regency during a certain period based on current business prices. The data collection process was carried out by obtaining secondary data based on the Kuantan Singingi District Statistics and Riau Province Statistics documents. During the analysis period, the agriculture, forestry, and fisheries sectors have become strong sectors in increasing the GRDP of Kuantan Singingi Regency. Mengidentifikasi sektor dan sub-sektor industri merupakan salah satu langkah dalam merencanakan pembangunan pusat pertumbuhan ekonomi. Oleh karena itu, analisis local quotient diperlukan untuk memahami seberapa jauh spesialisasi sektor ekonomi daerah tertentu dengan menggunakan sektor dasar atau unggulannya. Sektor basis dapat ditentukan dengan metode Local Quotient (LQ). Variabel yang digunakan untuk menentukan sektor ekonomi basis adalah Produk Domestik Regional Bruto (PDRB) untuk daerah yang kegiatannya difokuskan pada struktur finansial. Produk Domestik Bruto (PDB) adalah indikator penting untuk memahami kondisi ekonomi khususnya di Kabupaten Kuantan Singingi selama periode tertentu berdasarkan harga berlaku lapangan usaha. Proses pengumpulan data dilakukan dengan perolehan data sekunder berdasarkan dokumen Statistik Kabupaten Kuantan Singingi dan Statistik Provinsi Riau. Selama periode analisis, sektor pertanian, kehutanan, dan perikanan telah menjadi sektor yang kuat dalam meningkatkan PDRB Kabupaten Kuantan Singingi.